The Evaluation of the Relation between Bladder Cancer and Oxidative Stress Using NRF-2/KEAP-1 Pathway, Zinc and Copper Levels - Dogan, Cagri; Yazıcı, Cenk Murat; Akgül, Murat; Türker, Polat (Urology Journal, 2021)
Purpose: It has been shown that the Copper and Zinc contribute to the structure of the antioxidant enzymes. In addition NRF-2 and KEAP-1 complex have powerful effect on the intracellular organization of the antioxidants. We evaluated the relation of Copper, Zinc, NRF-2 and KEAP-1 complex regarding to the oxidative stress with tumor stage - grade in patients with bladder cancer. Materials and Methods: A total of 52 patients (32 bladder cancer and 20 control group) were included to the study. The demographic properties of groups were identical. Serum NRF-2, KEAP-1, Cu and Zn levels were compared by ELISA method between the groups and tissue NRF-2, KEAP-1, Cu and Zn levels were evaluated also by ELISA method at cancer patients.